Two new species of Coccophagus Westwood (Hymenoptera: Aphelinidae) from China - Zhang, Lan-Wei; Hu, Hong-Ying; Zhang, Yan-Zhou (Zootaxa, 2023)
The malthusi group of Coccophagus Westwood (Hymenoptera: Aphelinidae) is characterized by a densely setose mesoscutellum with the posterior apical pair of setae distinctly longer than others. In the present paper, two new species of the malthusi group are described from China: Coccophagus infuscatus sp. nov. and Coccophagus bandus sp. nov., both reared from species of Coccidae (Hemiptera: Sternorrhyncha). The type specimens are housed in Institute of Zoology, Chinese Academy of Sciences (IZCAS), Beijing, China.